2020
DOI: 10.21203/rs.3.rs-67713/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Influence of Substrate When Growing Tumorspheres

Abstract: Background: Cancer stem cells are important for the development of many solid tumors. These cells receive promoting and inhibitory signals that depend on the nature of their environment (their niche) and determine cell dynamics. Mechanical stresses are crucial to the initiation and interpretation of these signals. Methods: A two-population mathematical model of tumorsphere growth is used to interpret the results of a series of experiments recently carried out in Tianjin, China, and extract information about th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…From the point of view of the populations, the last two possibilities correspond to the birth of a new DCC, the parent cell either keeping (in the asymmetric duplication) or losing (in the symmetric case) its stemness. For example, writing the corresponding population dynamics differential equations, Benítez et al showed that a CSC will give birth to another CSC at a rate rp s which is estimated by fitting their mathematical model to the experimental data [9,10]. Since the probability of self-replication p s seems to be small in homeostasis and in most common culture media, then rp s will also be small, leading to quiescence, a main feature of CSCs.…”
Section: -1mentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of the populations, the last two possibilities correspond to the birth of a new DCC, the parent cell either keeping (in the asymmetric duplication) or losing (in the symmetric case) its stemness. For example, writing the corresponding population dynamics differential equations, Benítez et al showed that a CSC will give birth to another CSC at a rate rp s which is estimated by fitting their mathematical model to the experimental data [9,10]. Since the probability of self-replication p s seems to be small in homeostasis and in most common culture media, then rp s will also be small, leading to quiescence, a main feature of CSCs.…”
Section: -1mentioning
confidence: 99%
“…The addition of stem cell maintenance factors such as EGF or bFGF to the culture medium is an example of this case. These limiting situations were previously studied both experimentally [11,18] and mathematically [9,10], focusing in the first case on technical aspects of the assay, and in the second case on recovery of the CSC fraction.…”
Section: Simulation Of Two-dimensional Coloniesmentioning
confidence: 99%